Different keratoconus definitions can lead to substantial prevalence disparities in population-based studies - Hasan Shabani; Bart T. H. van Dooren; Magda A. Meester-Smoor; Annette A. J. M. Geerards; Caroline C. W. Klaver; Wishal D. Ramdas (Scientific Reports)
Abstract This report explores the prevalence of keratoconus in a population-based cohort of adults aged 40 or older according to ten different definitions. All Rotterdam Study participants with reliable Pentacam scans and no prior corneal refractive surgery were cross-sectionally analysed (n = 2660). First, we applied a novel evidence-based definition. Suspected keratoconus was defined as having at least one eye with a final D-index (BAD-D) ≥ 2.6. Manifest keratoconus was defined as having at least one eye with: (1) BAD-D ≥ 2.6; and (2) a score of at least 4/10 on the novel Rotterdam Keratoconus Scale (RKS); and (3) a confirming assessment of the relevant Pentacam maps; and (4) meeting Holladay’s criteria in case of recent contact lens usage. Using this proposed definition, 72 participants (2.71%, 95%CI: 2.16–3.40%) had suspected keratoconus, while 10 participants (0.38%, 95%CI: 0.20–0.69%) had manifest keratoconus. To assess reproducibility, two specialists independently applied the proposed definition, with a substantial inter-observer agreement (Kappa = 0.74). Interestingly, 6(60%) patients were unaware of having keratoconus. Applying nine alternative definitions from similar screening studies produced prevalence estimates ranging from 0.19 to 9.29% in the same cohort. Moreover, counting solely on a BAD-D cutoff of 2.6 to define keratoconus was unreliable, with a low positive predictive value of 14%. These findings explain partially the large heterogeneity in the reported keratoconus prevalences, underscoring the need for a standardized definition.